A Comparison of the Reactivating and Therapeutic Efficacy of Two Newly Developed Oximes (K727 and K733) with Oxime K203 and Trimedoxime in Tabun‐Poisoned Rats and Mice. (24th October 2014) - Kassa, Jiri; Sepsova, Vendula; Tumova, Martina; Horova, Anna; Musilek, Kamil
Abstract The reactivating and therapeutic efficacy of three original bispyridinium oximes (K727, K733 and K203) and one currently available oxime (trimedoxime) was evaluated in tabun‐poisoned rats and mice. The oxime‐induced reactivation of tabun‐inhibited acetylcholinesterase was measured in diaphragm and brain of tabun‐poisoned rats. The results showed that the reactivating efficacy of two recently developed oximes (K727 and K733) does not achieve the level of the reactivation of tabun‐inhibited acetylcholinesterase induced by oxime K203 and trimedoxime. While all oximes studied were able to increase the activity of tabun‐inhibited acetylcholinesterase in diaphragm, oxime K733 was not able to reactivate tabun‐inhibited acetylcholinesterase in the brain. The therapeutic efficacy of all oximes studied roughly corresponds to their reactivating efficacy. While both recently developed oximes were able to reduce acute toxicity of tabun less than 1.5‐fold, another original oxime K203 and commonly used trimedoxime reduced the acute toxicity of tabun almost two times. In conclusion, the reactivating and therapeutic potency of both newly developed oximes does not prevail the effectiveness of oxime K203 and trimedoxime, and therefore, they are not suitable for their replacement of commonly used oximes for the antidotal treatment of acute tabun poisoning.